The Effect of Using Skill Exercises Based on Generative Learning on Learning and Retaining Handling and Shooting Skills in Handball for Students - Nassr Khalid Abdulrazzaq; Saleh Ali dnhash; Abbas Abdul Hamza Kazem; Ali Yahya Abdulrzaq (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify the effect of using skill exercises based on generative learning in learning and retaining the skills of handling and shooting in handball among second-stage students at the College of Physical Education and Sports Sciences, Anbar University. The researchers used the experimental approach to suit the nature of the research, and the research sample consisted of the second stage students in the College of Physical Education, who numbered (80) students, and they were divided into two experimental groups that underwent a skill exercise program based on the foundations of generative learning, and a control that used the traditional method. Skill tests were applied before and after a retention period to measure the level of learning and retention of the two skills, and the program was applied for two months. The results showed that the experimental group significantly excelled in the skill performance tests and in the retention test, which indicates the effectiveness of skill exercises based on generative learning in enhancing students’ learning and retention of basic skills in handball.